Work Values and Employee Effort : A Needs-Supplies Fit Perspective - Abdelmoteleb, Samir A., (Colegio Oficial de Psicólogos de Madrid, 2020)
This study aimed to investigate the impact of work values (i.e., autonomy, competence and growth, and job security) on employee effort from a needs-supplies fit perspective. Using data from 295 employees and their 57 supervisors in two organizations, the results indicated that employee effort increased as employees' perceived values increased toward their preferred values. Moreover, employee effort did not show consistent patterns when the perceived work values exceeded the preferred values. Specifically, regarding autonomy and competence and growth, employee effort continued to increase as the perceived values exceeded the preferred values. However, regarding job security, employee effort declined as the perceived values substantially exceeded the preferred values. Furthermore, this study found that the higher the fit level between the perceived and preferred values, the greater the employee effort. Nevertheless, the findings regarding job security, which were inconsistent with our expectations, revealed that a considerably higher fit led to a decline in employee effort.